2016
DOI: 10.18632/oncotarget.10233
|View full text |Cite
|
Sign up to set email alerts
|

Aurora kinase A revives dormant laryngeal squamous cell carcinoma cells via FAK/PI3K/Akt pathway activation

Abstract: Revival of dormant tumor cells may be an important tumor metastasis mechanism. We hypothesized that aurora kinase A (AURKA), a cell cycle control kinase, promotes the transition of laryngeal squamous cell carcinoma (LSCC) cells from G0 phase to active division. We therefore investigated whether AURKA could revive dormant tumor cells to promote metastasis. Western blotting revealed that AURKA expression was persistently low in dormant laryngeal cancer Hep2 (D-Hep2) cells and high in non-dormant (T-Hep2) cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…In our previous study, we indicated that LSCC might activate FAK/PI3K/Akt pathway to promote metastasis . FAK was the molecule involved in proliferation, migration, and invasion .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In our previous study, we indicated that LSCC might activate FAK/PI3K/Akt pathway to promote metastasis . FAK was the molecule involved in proliferation, migration, and invasion .…”
Section: Discussionmentioning
confidence: 97%
“…Recently, dormant state reactivation, the phenomenon in which residual disease was existent, but asymptomatic, might be played a great role in the metastasis of multiple cancers, for instance breast, prostate, and lung . Moreover, AURKA might activate dormant state to promote the metastasis of LSCC . Wang stated that dormant cancer cells might contain high levels of drug resistant genes .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that PTEN and AURKA share certain common signaling pathways in malignant tumors (26)(27)(28)(29)(30)(31). Therefore, the present study analyzed the expression of PTEN in MGc803 and SGc7901 cells.…”
Section: Resultsmentioning
confidence: 93%
“…Polymorphisms in the AURKA gene have been shown to increase the risk of primary breast cancer (26). Studies have revealed that the increased expression of AURKA is associated with laryngeal, nasopharyngeal and breast cancer metastasis (27)(28)(29)(30). AURKA has been demonstrated to be accountable for the phosphorylation of Breast Cancer 1, Early Onset (BRCA1) (31).…”
Section: Discussionmentioning
confidence: 99%